STUDI KINETIKA DAN KARAKTERISASI HASIL SINTESIS ALKYD RESIN DARI GLISEROL DAN ASAM ADIPAT YANG TERMODIFIKASI MINYAK BIJI KARET - , Desi Nurandini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Alkyd resin modification with vegetable oil is intensively developed to be applied in paints and coatings industry. This research is aimed to study the reaction kinetics of alkyd resin synthesis from glycerol and adipic acid, modified with rubber seed oil, as well as to study the characteristics of alkyd resin products. Alkyd resin synthesis was carried out via monoglyceride process, which consisted of two stages reaction. The first stage was alcoholysis reaction of rubber seed oil with glycerol, produced monoglyceride. The reaction was conducted in three-neck flask with constant stirring speed and temperature. Variables studied were temperature (220Â°C - 260Â°C) and equivalent ratio OH/COOH 1,0 â 1,3 mgek/mgek. Samples were taken every 30 minutes during 3 hours, and then were analyzed their free glycerol content by alkalimetric titration method. Esterification was started by adding adipic acid to first stage product in batch reactor. The reaction was conducted under vacuum condition with temperature range of 220Â°C - 260Â°C and equivalent ratio OH/COOH 1,0 â 1,3 mgek/mgek. Samples were taken every 15 minutes for total of 75 minutes, and then were analyzed their hydroxyl content by uncatalyzed acetic anhydride method. The results showed that proposed kinetics model could describe well reaction of alcoholisis and esterification in synthesis of rubber seed oil-modified alkyd resin. The reaction rate constants were obtained as follows: Alcoholysis reaction: k1 = 2450 e (-10073/T) g/(mmol.min) k2 = 0,201 e (-4353/T) g/(mmol.min) k3 = 490 e (-9289/T) g/(mmol.min) Esterification reaction: k4 = 4820 e (-7547/T) g/(mgek.min) The characterization of alkyd resin product showed that equivalent ratio OH/COOH (Rek) affected the product characteristics. Based on the FTIR analysis, the presence of esters, hydroxyl and carboxylic acid groups were found. The acid value test showed that acid value of alkyd resin product decreased by increasing of Rek. The viscosity test gave result that the viscosity increased when Rek increased, which indicated that relative molecular weight of polymer increased along with increasing of Rek. Keywords: alkyd resin, alcoholysis, esterification, rubber seed oil, glycerol, adipic acid